Safe laparoscopic surgery in median arcuate ligament syndrome - Ulaş Aday; Abdullah Böyük; Barış Gültürk; Mehmet Buğra Bozan (Videosurgery and Other Miniinvasive Techniques)
The median arcuate ligament syndrome is a rare clinical condition with no standardized method of laparoscopic treatment. Exposure of the aorto-celiac axis might be considered as the most challenging part of the surgical procedure. It is important to secure total release while enabling adequate vision as the compressing musculofibrous ligament is located in the deepest part of the aorto-celiac hiatus. A 29-year-old male patient presenting with recurrent abdominal pain and diagnosed with the median arcuate ligament syndrome underwent laparoscopic surgery. The patient was discharged without problems on the fourth day after the surgery. In this case report we present a maneuver that enables easy and safe exposure of the celiac trunk.